Rumah Sejahtera Strategy as an Independent Entrepreneur by PKH Tembesi Members - Alifia Lisda Zetty Aqmi; Renny Christiarini (Universitas Internasional Batam, 2023)
This study aims to analyze the development of finished products from cassava at Pondok Tani located in Tembesi Village, Batam City. The problem find in this study is the low farmer wage rates resulting from the sale of crops only in the form of raw goods and finished goods which are less innovative. The research method uses research analysis methods through SWOT analysis, USP analysis, observation, interviews and documentation directly to the location. The results of this study refer to product development, namely MOCAF (Modified Cassava Flour) in line with government programs, namely local food diversification and a focus on products made from cassava. With this Rumah Sejahtera program, it can help organize the duties and responsibilities of Rumah Sejahtera members and increase sales results by 3,2%. Recommendations for further research are increasing the processing of MOCAF (Modified Cassava Flour) into other processed products.